Simulações computacionais de sistemas eletrônicos em geometrias confinadas - Venturini, Patricia Cristina (2008)
In this work, structural and dynamic properties of a two-dimensional electron system trapped to helium film, deposited on a solid substrate, are determined through molecular dynamics simulation. The influence of the film thickness and type of substrate on those properties are analyzed in the numerical experiments. A special attention is given to dynamical structure factor that is used to obtain some important properties of this system, like dispersion and mobility of electrons. For the first time, the dynamic structure factor from interacting electron system is applied to the calculus of mobility, introducing a many body effect.